Acute intestinal obstruction by Meckel’s diverticulum in adults - Estape, Gonzalo; Soto, Jose A.; Belloso, Rogelio; Castiglioni, Juan A. (Cirugía del Uruguay, 1974)
The authors report ffour cases of acute intestinal oclussion far Meckel diverticules. They point out: that this pathology is unusual in the adults, the difficulties of the preoperative diagnosis, the showed by sorne of the patients, the necessity of an urgent surgical intervention; and they analize ali the mechanisms of the production of the oclussion.